THE IMPACT OF SLEEP ON ENDURANCE ADAPTATIONS AND WEIGHT LOSS DURING RUNNING TRAINING IN OVERWEIGHT ADULTS: REVIEW - Jan Kamiński; Małgorzata Piekarska-Kasperska; Anna Daniel; Kacper Jankowski; Natalia Kraciuk; Alicja Bury; Karol Bartecki; Julia Błoniecka; Katarzyna Krupa; Sebastian Rurka (International Journal of Innovative Technologies in Social Science, 2025)
Sleep rarely receives as much attention as training or diet, yet it significantly influences how effective running programs are for weight loss, especially in adults with overweight or obesity. Poor sleep quality and insufficient sleep duration, common in this population, consistently limit improvements in aerobic fitness, reduce the effectiveness of fat loss, and slow down recovery after exercise. In contrast, better sleep habits support quicker endurance gains, more efficient recovery, and healthier body composition changes. Even simple interventions, such as maintaining regular sleep schedules, limiting screen use before bedtime, and improving overall sleep hygiene, can substantially improve training outcomes. This review highlights sleep as an essential component of successful running-based weight-loss interventions. Trainers and healthcare professionals should prioritize sleep improvement strategies to maximize exercise benefits. However, future research with larger groups and longer follow-up periods is necessary to confirm these findings and clarify optimal sleep interventions. Methods: This narrative review was conducted by searching PubMed, Scopus, and Web of Science for studies published between 2010 and 2025. The search used combinations of the terms sleep, running, endurance training, obesity, and weight loss. Studies were eligible if they included adults with overweight or obesity participating in running programs and reported outcomes related to endurance, recovery, or body composition. Randomized trials, observational research, and review articles were considered. Results: The reviewed studies consistently show that poor or insufficient sleep limits the benefits of running‑based programs in adults with overweight and obesity. Participants sleeping less than 7–8 hours often achieved smaller gains in aerobic fitness, recovered more slowly, and experienced less favorable body composition changes, including greater loss of lean mass. In contrast, good sleep habits were linked to better endurance improvements, more efficient recovery, and greater fat loss. Even simple steps like keeping a regular bedtime appeared to improve training adherence and outcomes. Still, most studies were small and short‑term, underlining the need for larger, long‑term research. Conclusions: Sleep clearly matters for adults with overweight or obesity who take up running to lose weight. When sleep quality or duration is compromised, the benefits of training are noticeably reduced, improvements in endurance come more slowly, recovery takes longer, and fat loss is less efficient. Conversely, maintaining good sleep habits appears to amplify the positive effects of running programs, making progress faster and more sustainable. From a practical standpoint, trainers and clinicians should consider sleep not just as a passive recovery process, but as an active part of effective weight-management strategies. Simple recommendations like regular sleep schedules or better sleep hygiene may lead to substantial improvements in training outcomes. Future studies should further clarify how targeted sleep interventions can enhance exercise-based programs in this population.